Electrochemical oxidation of a real effluent using selective cathodic and anodic strategies to simultaneously produce high value-added compounds: Green hydrogen and carboxylic acids - Oliveira, Herbet L.; Barros, Thalita M.; Santos, José E.L. [UNESP]; Gondim, Amanda D.; Quiroz, Marco A.; Martínez-Huitle, Carlos A. [UNESP]; dos Santos, Elisama V. [UNESP] (Elsevier, 2023)
In this work, the simultaneous production of green hydrogen (H2) and carboxylic acids from the electrochemical treatment of washing machine effluent is demonstrated for the first time. The electrochemical treatment of the effluent was carried out using a solar-powered polymer electrolyte membrane (PEM-type) cell with a boron-doped diamond (BDD) electrode as anode and a Ni-Fe-based SS (stainless steel) mesh as the cathode with two types of electrolytes (0.1 mol/L H2SO4 and 0.1 mol/L Na2SO4), by applying different current densities (j). A synthetic and non-destructive effluent transformation strategy was implemented by controlling the operating conditions in order to regulate precursor-intermediates, oxidants, and •OH production. The results show the formation of high value-added products (carboxylic acids) and energy sources (green H2) in the anodic and cathodic compartments, respectively, with the possibility of selective electroconversion to acetic acid depending on the electrolyte and j. The green H2 production rate is also influenced by the pH conditions, the electrolyte, and the anodic j. The technology proposed here may constitute a promising, efficient and sustainable route towards the United Nations’ Sustainable Development Goals (SDGs) 6 and 7.
Keywords: Circular economy; Diamond electrode; Electro-refinery; Green hydrogen; High value-added products; Washing machine effluent